Afferent fibres from pulmonary arterial baroreceptors in the left cardiac sympathetic nerve of the cat - Nishi, K. (1974)
1. Afferent discharges were recorded from the left cardiac sympathetic nerve or the third sympathetic ramus communicans of anaesthetized cats. Twenty-one single units with baroreceptor activity were obtained. 2. The receptors of each unit were localized to the extrapulmonary part of the pulmonary artery, determined by direct mechanical probing of the wall of the pulmonary artery after death of the animals. Conduction velocity of the fibres ranged from 2·5 to 15·7 m/sec. 3. Afferent discharges occurred irregularly under artificial ventilation. The impulse activity was increased when pulmonary arterial pressure was raised by an intravenous infusion of Locke solution, or by occlusion of lung roots, and decreased by bleeding the animal from the femoral artery. 4. Above a threshold pressure, discharges occurred synchronously with the systolic pressure pulse in the pulmonary artery. A progressive further rise in pressure did not produce an increase in the number of impulses per heart beat. Occlusion of lung roots initially elicited a burst of discharges but the number of impulses for each cardiac cycle gradually decreased. 5. The receptors responded to repetitive mechanical stimuli up to a frequency of 10/sec, but failed to respond to stimuli delivered at 20/sec. 6. The results provide further evidence for the presence of afferent fibres in the cardiac sympathetic nerve. These afferent fibres are likely to provide the spinal cord with specific information only on transient changes in pulmonary arterial pressure.